Implementation of the Service Strategic Plan at the Nene Mallomo Regional General Hospital - Risnanda Thamrin; Arni Rizqiany Rusydi; Yusriani Yusriani (Jurnal EduHealth, 2023)
Background: Hospitals are one of the most important parts of the health care system. The hospital functions as a referral place from other referral places, so the hospital as a health service institution also carries out health efforts with a preventive, promotive, curative and rehabilitative approach. This research aims to describe, summarize various conditions, various situations, or various phenomena of reality that are happening in society. Method: This research uses qualitative techniques with a descriptive approach. The instruments used are interview guidelines, notebooks, stationery, recording devices and cameras. The research was conducted in July-August 2022. The main informants in this study were the Deputy Director of Services, Head of Planning and Programs, Head of Service, and Head of General and Administrative Subdivisions. In addition, the main informants in this study also included staff at RSUD Nene Mallomo. Results: There are steps taken by Nene Mallomo Hospital in Sidrap Regency, which is one of the steps taken to analyze the conditions in the hospital both from an external and internal perspective. However, at the time of making the strategic plan that was carried out, it also paid attention to the law and also various ministerial regulations to regional regulations,